Emergency medical technician - Aehlert, Barbara (McGraw Hill, 2009)
This workbook provides you with an opportunity to review and master the concepts and skills introduced in Barbara Aehkert's textbook, Emergency Medical Technician: EMT in Action, 1e. Together, your textbook and this workbook form a complete learning package. Emergency Medical Technician: EMT in Action , First Edition, will help you prepare to provide safe and immediate patient care and to work effectively as part of an EMS team